Advances in mechanisms of resistance to aromatase inhibitors. Issue 4 (April 2014) - Chumsri, Saranya; Schech, Amanda; Chakkabat, Chakkapong; Sabnis, Gauri; Brodie, Angela
<x xml:space="preserve">Abstract</x> Clinically, there are two distinct types of aromatase inhibitor (AI) resistance, namely acquired and innate resistance. Because the underlying mechanisms of these two types of resistance may not be mutually exclusive, strategies to tackle these resistances may not be effective when used interchangeably. Activation of growth factor receptor pathways is the hallmark of acquired AI resistance. These pathways can be targeted either at the cell surface receptor level or their downstream signaling cascades. Currently, everolimus in combination with exemestane represents a new standard of care for patients progressing on non-steroidal AIs. HDAC inhibitors have also shown promising results For innate resistance, the combination of fulvestrant and AI in the front line setting represents a new treatment option, particularly for patients who present with de novo metastatic disease. A Phase III trial is currently ongoing to evaluate the benefit of CDK 4/6 inhibitor, palbociclib, in the first line setting in combination with AI.